DINAMIKA MERGERNYA BANK SYARIAH TERBESAR DI INDONESIA - Aldiansyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Merger means the merging of several companies, or also known as a process of merging a company that is deemed to have less than optimal performance into a company that has maximum or good performance, causing the company to merge and then dissolve, where the whole is a legal process. The merger of Bank Syariah Indonesia is expected to be a solution to the weak economic system. The purpose of this study is to determine the regulation of the merger of Islamic banks in Indonesia to become an Indonesian Islamic bank and to determine the dynamics and legal impact of the merger of Indonesian Islamic banks on the stability of economic policy in Aceh. The method used in this research is descriptive research, and the object of this research is taken from one of the Islamic banking in Indonesia, namely PT. Bank Syariah Indonesia (BSI) Meulaboh Imam Bonjol Branch. This research is a qualitative research because in the process of collecting data the researcher must conduct a review stage of secondary data originating from literature, journals, books, articles and others. The results of this study are the regulation of the implementation of the merger that can be carried out by complying with every applicable law, the dynamics of the merger of Bank Syariah Indonesia which began with the establishment of Bank Islam Malaysia Berhad (BIMB) in 1983 until finally in 2020, and the legal impact the merger of Bank Syariah Indonesia on the stability of economic policy in Aceh which has positive and negative impacts.